Between love and boycott: a story of dual origin brands. Issue 3 (4th November 2020) - Abdelwahab, Dalia; Jiménez, Nadia; San-Martín, Sonia; Prodanova, Jana
Abstract : Purpose: This research aims to address ethnocentric consumers' willingness to boycott dual origin brands, in the particular case of national brands linked to a very specific regional origin, through analysing the paradox of (unfavourable) regional ethnocentrism versus (favourable) consumer–brand relationship (i.e. brand identification, trust and love) on consumers' decision to buy or boycott those brands in that circumstances. Building on social identity and cognitive dissonance theories, this study aims to examine the Spanish consumer relationship with national brands originated in Catalonia considering the current conflicting circumstances in the region. Design/methodology/approach: The authors collected data by means of personal questionnaires, distributed among 277 Spanish consumers of Catalan brands of Cava. The data is analysed by using structural equation modelling and linear structural relations. Findings: After controlling for brand familiarity, the results of this study reveal that ethnocentrism negatively distorts consumers' confidence in dual origin brands and highlight the role of identification and trust as brand love antecedents. It also reveals that ethnocentrism has a more profound impact on boycotting decision than brand love. Originality/value: This study is one of the few to capture the puzzlement created by the paradoxical nature of the brand's duality of origin. Furthermore, it contributes to the marketing literature by examining the impact of ethnocentrism on two relationship variables (i.e. identification and trust) and exploring their joint impact on consumers' decision to buy or boycott. The findings of this study can be helpful for companies facing boycotting behaviour triggered by ethnocentric consumer reaction towards dual origin brands. Abstract : Propósito: Esta investigación tiene como objetivo abordar la disponibilidad de los consumidores etnocéntricos para boicotear las marcas de origen dual -en el caso particular de marcas nacionales vinculadas a un origen regional muy específico-, mediante el análisis de la paradoja del (desfavorable) etnocentrismo regional versus la relación (favorable) entre el consumidor y la marca (es decir, la identificación, la confianza y el amor a la marca) en la decisión de los consumidores de comprar o boicotear dichas marcas en esas circunstancias. Partiendo de las teorías de la identidad social y la disonancia cognitiva, este estudio examina la relación del consumidor español con las marcas nacionales originales de Cataluña, considerando las circunstancias conflictivas actuales en la región. Diseño/método: Los datos se recogieron mediante cuestionarios personales, distribuidos entre 277 consumidores españoles de marcas catalanas de Cava. Los datos se analizaron utilizando modelación de ecuaciones estructurales y relaciones estructurales lineales. Hallazgos: Después de controlar la familiaridad con la marca, nuestros resultados revelan que el etnocentrismo distorsiona negativamente la confianza de los consumidores en las marcas de origen dual y destaca el papel de la identificación y la confianza como antecedentes del amor por la marca. También revela que el etnocentrismo tiene un impacto más profundo en la decisión de boicotear que el amor por la marca. Originalidad/valor: Este estudio es uno de los pocos que captura la confusión creada por la naturaleza paradójica de la dualidad del origen de la marca. Además, contribuye a la literatura de marketing al examinar el impacto del etnocentrismo en dos variables relacionales (la identificación y la confianza) y explorar su impacto conjunto en la decisión de los consumidores de comprar o boicotear. Nuestros hallazgos pueden ser útiles para las empresas que se enfrentan al comportamiento de boicot provocado por la reacción etnocéntrica de los consumidores hacia las marcas de origen dual.